2020
DOI: 10.1038/s41467-020-16456-6
|View full text |Cite
|
Sign up to set email alerts
|

Causal effects of population dynamics and environmental changes on spatial variability of marine fishes

Abstract: Populations with homogeneous distributions have better bet-hedging capacity than more heterogeneously distributed populations. Both population dynamics and environmental factors may influence the spatial variability of a population, but clear empirical evidence of such causal linkages is sparse. Using 25-year fish survey data from the North Sea, we quantify causal effects of age structure, abundance, and environment on nine fish species. We use empirical dynamic modeling-an approach based on state-space recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…They have found negative relationships for Pacific sardine and Pacific chub mackerel at multiple time lags, Pacific hake at time lag of 11 years, and no relationship for bocaccio. Similarly, among eight exploited fish species on the North Sea, only Atlantic cod, plaice, and Atlantic mackerel exhibited negative causal relationships between age diversity and spatial variability of fish (Wang et al, 2020). Our findings from the individual-based model suggest that within the same marine ecosystem, the variability in species' spatial responses to age truncation is likely associated with their degree of age-specific habitat preference.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…They have found negative relationships for Pacific sardine and Pacific chub mackerel at multiple time lags, Pacific hake at time lag of 11 years, and no relationship for bocaccio. Similarly, among eight exploited fish species on the North Sea, only Atlantic cod, plaice, and Atlantic mackerel exhibited negative causal relationships between age diversity and spatial variability of fish (Wang et al, 2020). Our findings from the individual-based model suggest that within the same marine ecosystem, the variability in species' spatial responses to age truncation is likely associated with their degree of age-specific habitat preference.…”
Section: Discussionmentioning
confidence: 64%
“…Such an increase in variability in local abundances leads to an elevated population spatial variability at the landscape scale. This mechanism may explain empirical findings of the negative association between age structure and spatial variability of fishes (Kuo et al, 2016;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In contrast, whiting, haddock and saithe exhibit apparently humped shape relationship in both quarters yet with different steepness. Such differences suggested that the aggregation tendency not only could be affected by body size, but might also be determined by other biological traits, migratory behavior and fishing pressure at the species level (Kuo et al 2016, Wang et al 2020). For example, the different pattern between Q1 and Q3 for the pelagic species (herring, mackerel and sprat) might because they can quickly aggregate during spawning season while dispersing during the resting season (Daan et al 1990).…”
Section: Discussionmentioning
confidence: 99%